IMPLEMENTASI COLLABORATIVE INNOVATION DALAM PENINGKATAN KUALITAS PENDIDIKAN DI SEKOLAH - Nurfitriyanti, Maya; Hidayat, Rais (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to determine the implementation of collaborative innovation in improving the quality of education in schools. This study is a qualitative study using the Focus Group Discussion method. FGD was conducted on several teachers at one of South Jakarta's junior high schools with different educational backgrounds. Based on the results of the interview, it was found that innovation in education is very much needed. With innovation, teachers can be more creative in creating interesting learning and motivating students to learn. One form of innovation needed by teachers is collaborative innovation. With collaborative innovation, teachers' insights will increase and teachers will be able to create innovations in learning that can increase students' interest and motivation to learn. In addition, with collaborative innovation, teachers can learn new things outside their fields that can increase knowledge and improve the quality of education. Based on the results of the study, it can be concluded that collaborative innovation can improve the quality of education in schools, although the results of the increase are not significant, this is due to the background of students who are mostly not from academic achievement. However, with collaborative innovation, teachers maximize the learning process and there is an increase in students' willingness to learn.